2010
DOI: 10.1128/jvi.00573-10
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus LF2 Protein Regulates Viral Replication by Altering Rta Subcellular Localization

Abstract: The switch from Epstein-Barr virus (EBV) latent infection to lytic replication is governed by two viral transactivators, Zta and Rta. We previously reported that the EBV protein LF2 binds Rta, inhibits Rta promoter activation, and blocks EBV replication in cells. In addition, LF2 induces SUMO2/3 modification of Rta. We now show that this modification occurs at four lysines within the Rta activation domain (426, 446, 517, and 530) and that sumoylation of Rta is not essential for its repression. Coexpression stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 77 publications
1
29
0
Order By: Relevance
“…That synthesis of new viral DNA is not required for Rta interactions with late promoters narrows down the possibilities for cis or trans signals that direct Rta to late promoters (2,69). Chromatin changes in the parental episome, viral or cellular gene expression independent of viral DNA replication, Rta modifications, such as sumoylation (11,33), or translocation of the episome to nuclear sites, such as PML bodies (3), might play a role in the recruitment of Rta to late gene promoters. Recent studies in murine gammaherpesvirus 68 (MHV68) have demonstrated that late gene expression depends not only on DNA replication but also on a subset of genes present in beta-and gammaherpesviruses but absent in alphaherpesviruses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…That synthesis of new viral DNA is not required for Rta interactions with late promoters narrows down the possibilities for cis or trans signals that direct Rta to late promoters (2,69). Chromatin changes in the parental episome, viral or cellular gene expression independent of viral DNA replication, Rta modifications, such as sumoylation (11,33), or translocation of the episome to nuclear sites, such as PML bodies (3), might play a role in the recruitment of Rta to late gene promoters. Recent studies in murine gammaherpesvirus 68 (MHV68) have demonstrated that late gene expression depends not only on DNA replication but also on a subset of genes present in beta-and gammaherpesviruses but absent in alphaherpesviruses.…”
Section: Discussionmentioning
confidence: 99%
“…pcDNA3-Rta, pGL3-BALF2p, pGL3-BMLF1p, pGL3-BMRF1p, pGL3-Zp, and pGL3-Rp have been described previously (8,33). The BLRF2 (Ϫ349/ϩ28; B95-8 nucleotides 88548 to 88924), BFRF3 (Ϫ727/ϩ128; B95-8 nucleotides 60585 to 61439), and BALF5 (Ϫ376/ ϩ16; B95-8 nucleotides 156859 to 157250) promoters were amplified from B95-8 genomic DNA and cloned into the pGL3 promoter (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, sumoylation by SUMO-1 has been shown to increase Rta transactivation activity (Chang et al, 2004). It is also known that LF2 enhances Rta conjugation to SUMO-2 and SUMO-3 (Calderwood et al, 2008), but this is unrelated to LF2-mediated repression of Rta functions (Heilmann et al, 2010). However, we have found that SUMO-2-Rta can be ubiquitinated via RNF4, leading to decreased Rta stability during lytic progression .…”
Section: Introductionmentioning
confidence: 56%